Pengaruh Endorser Credibility terhadap Brand Equity ‘Shopee For Men’ dengan Self-Brand Connection sebagai Mediator - Ade Multi Davista Sari; Citra Kusuma Dewi (Akademi Sekretari Manajemen Taruna Bakti, 2019)
Shopee is one of the markets that provide online trading platforms in Indonesia. Shopee is known by consumers as a brand associated with brands only for women. Though Shopee is a neutral market and is aimed at all circles. Brand equity. This will have an impact on consumer preferences including male consumers of the Shopee brand. Shopee has a strategy by launching the